2024
DOI: 10.1021/acsenergylett.3c02763
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Perovskite Nanocrystals and Nanocomposites for Scintillation Applications

Abhinav Anand,
Matteo L. Zaffalon,
Andrea Erroi
et al.

Abstract: In recent years, the field of radiation detection has witnessed a paradigm shift with the emergence of plastic scintillators incorporating perovskite nanocrystals (PNCs). This innovative class of scintillators not only capitalizes on the superior luminescent properties of PNCs but also harnesses the flexibility and processability of polymers. This review explores the intricate landscape of synthesizing and fabricating scintillating PNCs and nanocomposites, delving into the methods employed in their production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 247 publications
0
2
0
Order By: Relevance
“…Scintillator materials play a pivotal role in a wide array of applications, ranging from radiation detection in the fields of nuclear physics, medical imaging, , and homeland security , to fundamental research in high-energy physics (HEP) . As the demand for efficient and versatile scintillators continues to grow, the quest for materials that exhibit superior performance characteristics intensifies. , Nanocomposite scintillators, a recent and promising development in this domain, have garnered significant attention for their potential to overcome the limitations of traditional scintillator crystals, which, although highly effective, face inherent limitations in terms of upscaling, cost-effectiveness, and timing performance . Conversely, commercial plastic scintillators, while cost-effective, versatile, and fast, exhibit limited performance in terms of energy resolution and radiation hardness due respectively to their low density and inherent fragility of conjugated molecular emitters to high-energy radiation .…”
Section: Synthesis and Resurfacing Of Cspbcl3 Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scintillator materials play a pivotal role in a wide array of applications, ranging from radiation detection in the fields of nuclear physics, medical imaging, , and homeland security , to fundamental research in high-energy physics (HEP) . As the demand for efficient and versatile scintillators continues to grow, the quest for materials that exhibit superior performance characteristics intensifies. , Nanocomposite scintillators, a recent and promising development in this domain, have garnered significant attention for their potential to overcome the limitations of traditional scintillator crystals, which, although highly effective, face inherent limitations in terms of upscaling, cost-effectiveness, and timing performance . Conversely, commercial plastic scintillators, while cost-effective, versatile, and fast, exhibit limited performance in terms of energy resolution and radiation hardness due respectively to their low density and inherent fragility of conjugated molecular emitters to high-energy radiation .…”
Section: Synthesis and Resurfacing Of Cspbcl3 Nanocrystalsmentioning
confidence: 99%
“…In this framework, lead halide perovskite NCs (LHP-NCs) have rapidly garnered particular interest ,,, due to their high emission yield, radiation hardness, , defect tolerance, and unmatched scalability via room-temperature synthesis methods . This unique combination of chemical and physical advantages has driven a large number of studies encompassing X-ray imaging, fast timing, ,,,, and therapy applications as well as the detection of γ rays and neutrons. ,, Despite substantial advancements, as of today, the near totality of studies in this area has focused on green-emitting CsPbBr 3 NCs, ,,,, with fewer investigations dedicated to their red-emitting iodine-based counterparts (mostly as single crystals or films for γ detection). Most surprisingly, there has been no study to date that has addressed the scintillation properties of CsPbCl 3 NCs, which feature size tunable ultrafast emission in the UV-blue , and would thereby extend the spectral tunability of LHP-based nanocomposite scintillators to the typical spectral region of molecular scintillators such as 1,4-bis­(5-phenyloxazol-2-yl) benzene (POPOP) (λ EM ≈ 410 nm) and p -terphenyl (λ EM ≈ 350 nm) that match the peak efficiency of bialkali photodetectors widely used in HEP experiments (e.g., Hamamatsu R9880U-210, see Figure S1 in the Supporting Information). , Further CsPbCl 3 NCs have the potential to serve as high- Z sensitizers for secondary molecular emitters in the green spectral region that typically suffer less radiation damage than the more energetic blue-emitting counterparts.…”
Section: Synthesis and Resurfacing Of Cspbcl3 Nanocrystalsmentioning
confidence: 99%
“…We refer to more dedicated literature focusing on the other effects affecting the reactivity of nanocatalysts [25,44,45]. Finally, it must be mentioned that the number of implications of quantum-size effects to the band gap of nanomaterials is not limited to catalysis only, as it may involve other fields such as optoelectronics, sensing, medical diagnostic etc [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, much work has demonstrated that doping strategies can efficiently modulate and stabilize PNC lattices and enhance exciton radiation recombination for luminescence. 20,21 Additionally, the luminescence properties of PNCs are significantly influenced by factors such as the crystal size, surface ligand type, and dangling bonding mode. 22,23 Therefore, corresponding modification strategies have been proposed to improve the luminescence of PNCs.…”
Section: Introductionmentioning
confidence: 99%